PERLAWANAN TERSELUBUNG DI TENGAH REGRESI DEMOKRASI (STUDI KASUS MURAL JALANAN DI KOTA SOLO DAN YOGYAKARTA) - Rashida Indira Prasanti; Nur Hidayat - Sardini; Turtiantoro - - (Journal of Politic and Government Studies, 2023)
Social, political, economic, and cultural dynamics, which remain to be interesting topics for discussion until now, have become one of the things that have received lots of public attention. People who should be the highest authority in a democratic country are competing to exercise their right to freedom of opinion and voice through various channels, including non-formal political channels using street art. The existence of street artists who are increasing every time adds to the understanding for the community that the definition of art is not only for art but also as art for politics. Using qualitative research methods with new social movement theory and the concept of covert resistance, this paper will reveal the results of an analysis of how murals that are included in street art play their function as covert resistance and media criticism, and what is the role of the state and apparatus in protecting freedom of opinion and expression of society . The results of the study show the fact that street murals exist because street artists who are also civil society voice their concerns and are relevant to many people in the situation that was happening at that time, and basically there are still difficulties for the political domination in accepting the presence of street art as one of the medium of resistance and criticism